2017
DOI: 10.1038/s41598-017-15878-5
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the delta neutrophil index to predict 30-day mortality in patients with ST segment elevation myocardial infarction

Abstract: This study aimed to evaluate the association between the delta neutrophil index (DNI), which reflects immature granulocytes, and the severity of ST-elevation myocardial infarction (STEMI), as well as to determine the significance of the DNI as a prognostic marker for early mortality and other clinical outcomes in patients with STEMI who underwent reperfusion. This retrospective, observational cohort study was conducted using patients prospectively integrated in a critical pathway program for STEMI. We included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Although several pro-inflammatory cytokines like IL-6 can be usefully applied in clinical situations, additional costs, time, and new equipment must be considered for single or repeated measurements to predict the severity of the patients’ conditions. Recent studies have explored the DNI as an adjunct predictor because inflammatory markers that can be measured rapidly, easily, serially, and inexpensively are an unmet need 9 , 26 . The automatically calculated DNI is a more prompt and accurate method than manually counting immature granulocytes 10 , 14 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although several pro-inflammatory cytokines like IL-6 can be usefully applied in clinical situations, additional costs, time, and new equipment must be considered for single or repeated measurements to predict the severity of the patients’ conditions. Recent studies have explored the DNI as an adjunct predictor because inflammatory markers that can be measured rapidly, easily, serially, and inexpensively are an unmet need 9 , 26 . The automatically calculated DNI is a more prompt and accurate method than manually counting immature granulocytes 10 , 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The automatically calculated DNI is a more prompt and accurate method than manually counting immature granulocytes 10 , 14 . Several studies have shown that an increased DNI is associated with poor outcomes in specific disease conditions and can predict the severity of infection and sterile inflammation 9 11 , 14 , 15 . Although the pathophysiologic mechanisms by which DNI values are associated with severity of disease are not fully understood, several studies have elucidated the mechanisms by which immature granulocytes are released early and rapidly during severe inflammation 9 , 15 , 26 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations